Highly fluorescent cucurbit[8]uril–perylenemonoimide host–guest complexes as efficient fluorescent probes for N-terminal phenylalanine. Issue 86 (31st August 2016) - Aryal, Gyan Hari; Huang, Liming; Hunter, Kenneth W.
Abstract : We have developed host–guest fluorescent complexes based on cucurbit[8]uril and a perylenemonoimide for selective and sensitive detection of N-terminal phenylalanine peptides. Abstract : We report host–guest fluorescent complexes based on cucurbit[8]uril (CB[8]) and water-soluble perylenemonoimidePMI-1 . The fluorescence of CB[8] : PMI-1 complexes reverses after the displacement with other guest molecules and they could serve as selective and sensitive probes for N-terminal phenylalanine peptides.